"But Amen is the Price:" James Baldwin and Ray Charles in "The Hallelujah Chorus". (29th September 2015) - Pavlić, Ed
Abstract : Based on a recent, archival discovery of the script, "But Amen is the Price" is the first substantive writing about James Baldwin's collaboration with Ray Charles, Cicely Tyson, and others in a performance of musical and dramatic pieces. Titled by Baldwin, "The Hallelujah Chorus" was performed in two shows at Carnegie Hall in New York City on 1 July 1973. The essay explores how the script and presentation of the material, at least in Baldwin's mind, represented a call for people to more fully involve themselves in their own and in each other's lives. In lyrical interludes and dramatic excerpts from his classic work, "Sonny's Blues, " Baldwin addressed divisions between neighbors, brothers, and strangers, as well as people's dissociations from themselves in contemporary American life. In solo and ensemble songs, both instrumental and vocal, Ray Charles's music evinced an alternative to the tradition of Americans' evasion of each other. Charles's sound meant to signify the history and possibility of people's attainment of presence in intimate, social, and political venues of experience. After situating the performance in Baldwin's personal life and public worldview at the time and detailing the structure and content of the performance itself, "But Amen is the Price" discusses the largely negative critical response as a symptom faced by much of Baldwin's other work during the era, responses that attempted to guard "aesthetics" generally—be they literary, dramatic, or musical—as class-blind, race-neutral, and apolitical. The essay presents "The Hallelujah Chorus" as a key moment in Baldwin's search for a musical/literary form, a way to address, as he put it, "the person and the people, " in open contention with the social and political pressures of the time.